Sparsity enhancing wavelets design for ECG and fetal ECG compression. (January 2022) - Abhishek, S.; Veni, S.
Highlights: Reviews comments addressed as suggested by respected reviewer. Length of the paper shortened as suggested by respected reviewer. Execution time comparison between 'dew1' and 'dew2'. Abstract: This paper details the design of a set of wavelet filters that are bi orthogonal in nature. The designed wavelets are experimented in publicly available MIT data base. In Compressed Sensing (CS) paradigm reconstruction quality can be improved by improving the sparsity. From experiments it was found that ECG records especially fetal ECGs have a better sparse representation in the newly designed domain as compared to commonly used wavelets. This paper also details the fundamentals of CS in a much easier way and briefly reviews some state of art methods in CS based on ECG reconstruction scenarios. The best state of art method in terms of reconstruction quality is selected for testing the designed wavelets. The designed wavelet is named as 'dew2'.The design details of this bi orthogonal wavelet system are detailed in different sections with the help of standard wavelet system design rules.